An Clinical Study on Finding Hypothermia and Postpartum Haemorrhage Using Temperature - V.D. , Ambeth Kumar; S. , Sharmila (International Journal of Psychosocial Rehabilitation, 2020)
Hypothermia is the reduction of body temperature, which is in the range of below 370°C. Severe and life-threatening hypothermia will happen when the body temperature goes below 300°C, which will affect pregnant women after deliveries. The novelty is to find hypothermia-affected patients using wearable devices. After delivery, this device will measure the body temperature of pregnant women. The measured value is compared to the normal temperature value. If the value is less than the normal level, then the values should be intimated to the doctor or nurse through IoT. Using Fuzzy techniques the predicted values from pregnant women will be used to predict the hypothermia affected patients